A Replicating Single-Cycle Adenovirus Vaccine Effective against Clostridium difficile - William E. Matchett; Stephanie Anguiano-Zarate; Goda Baddage Rakitha Malewana; Haley Mudrick; Melissa Weldy; Clayton Evert; Alexander Khoruts; Michael Sadowsky; Michael A. Barry (Vaccines, 2020)
Clostridium difficile causes nearly 500,000 infections and nearly 30,000 deaths each year in the U.S., which is estimated to cost $4.8 billion. C. difficile infection (CDI) arises from bacteria colonizing the large intestine and releasing two toxins, toxin A (TcdA) and toxin B (TcdB). Generating humoral immunity against C. difficile’s toxins provides protection against primary infection and recurrence. Thus, a vaccine may offer the best opportunity for sustained, long-term protection. We developed a novel single-cycle adenovirus (SC-Ad) vaccine against C. difficile expressing the receptor-binding domains from TcdA and TcdB. The single immunization of mice generated sustained toxin-binding antibody responses and protected them from lethal toxin challenge for up to 38 weeks. Immunized Syrian hamsters produced significant toxin-neutralizing antibodies that increased over 36 weeks. Single intramuscular immunization provided complete protection against lethal BI/NAP1/027 spore challenge 45 weeks later. These data suggest that this replicating vaccine may prove useful against CDI in humans.